2000
DOI: 10.1097/00000658-200007000-00019
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Pseudomonas aeruginosa PA-I Lectin on Experimental Gut-Derived Sepsis

Abstract: ObjectiveTo examine the effect of Pseudomonas aeruginosa on intestinal barrier function and its lethal potential when introduced into the intestinal tract of mice. Summary Background DataThe mere presence of P. aeruginosa in the intestinal tract of critically ill patients is associated with a threefold increase in death compared with matched cohorts without this pathogen. Whether this effect is a cause or a consequence of the critically ill state has not been previously addressed. MethodsTransepithelial electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
90
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 37 publications
(32 reference statements)
4
90
0
1
Order By: Relevance
“…In a different setting, the contribution of LecA to virulence was evaluated in an intestinal injury model. In this murine model, the combination of LecA and exotoxin A led to a high rate of mortality at 48 h after inoculation; however, no mortality was observed when these two virulence factors were inoculated separately (19). These results suggest that LecA acts in synergy with other virulence factors.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In a different setting, the contribution of LecA to virulence was evaluated in an intestinal injury model. In this murine model, the combination of LecA and exotoxin A led to a high rate of mortality at 48 h after inoculation; however, no mortality was observed when these two virulence factors were inoculated separately (19). These results suggest that LecA acts in synergy with other virulence factors.…”
Section: Discussionmentioning
confidence: 61%
“…The galactophilic molecule LecA has been shown to have a cytotoxic effect on respiratory epithelial cells by decreasing their growth rate, thus contributing to respiratory epithelial injury (2). In addition, it has been demonstrated that LecA induces a permeability defect in the intestinal epithelium, resulting in increased absorption of exotoxin A, an important extracellular virulence factor (19). Additionally, relationships between lectins and other virulence factors have been shown; for example, LecB was shown to be involved in pilus biogenesis and protease IV activity (29).…”
mentioning
confidence: 99%
“…A number of studies have aimed to elucidate the role of mucosal membranes in the pathogenesis of sepsis and subsequent aggravation of the condition (14,21,63). Hypothetically, a reduced intestinal barrier function could lead to translocation of intraluminal bacteria and their dissemination to various internal tissues followed by secondary infections and multiple organ dysfunction syndrome (3,12).…”
Section: Discussionmentioning
confidence: 99%
“…The opportunistic pathogen Pseudomonas aeruginosa synthesizes two lectins, LecA and LecB (also known as PA-IL and PA-IIL), with specificity for galactose and fucose, respectively. Many roles have been suggested for these lectins, including adhesion of the bacterium to airway epithelial cells and injury to cells (1,15). Furthermore, LecB was recently reported to be involved in biofilm formation (27).…”
mentioning
confidence: 99%